2019
DOI: 10.3390/cancers11030280
|View full text |Cite
|
Sign up to set email alerts
|

Observed Survival Interval: A Supplement to TCGA Pan-Cancer Clinical Data Resource

Abstract: To drive high-quality omics translational research using The Cancer Genome Atlas (TCGA) data, a TCGA Pan-Cancer Clinical Data Resource was proposed. However, there is an out-of-step issue between clinical outcomes and the omics data of TCGA for skin cutaneous melanoma (SKCM), due to the majority of metastatic samples. In clinical cases, the survival time started from the initial SKCM diagnosis, while the omics data were characterized at TCGA sampling. This study aimed to address this issue by proposing an obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The melanoma cohort in the TCGA database contains primary and metastatic samples. Specifically, TCGA did not always adopt the initially diagnosed melanoma samples for sequencing (Xiong et al, 2019). The majority of the primary samples submitted to sequence were initially diagnosed melanoma samples, and the majority of the metastatic samples for sequencing were from follow-up patients instead of initially diagnosed samples.…”
Section: Introductionmentioning
confidence: 99%
“…The melanoma cohort in the TCGA database contains primary and metastatic samples. Specifically, TCGA did not always adopt the initially diagnosed melanoma samples for sequencing (Xiong et al, 2019). The majority of the primary samples submitted to sequence were initially diagnosed melanoma samples, and the majority of the metastatic samples for sequencing were from follow-up patients instead of initially diagnosed samples.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the potential pathology of synchronous MPM needs to be illustrated in the future. Furthermore, many molecular events such as mutation (Demunter et al, 2001;Griewank et al, 2014), copy number variation (Rákosy et al, 2010;Gerami et al, 2011), epigenetic variation (Roh et al, 2016;Wouters et al, 2017), expression of genes (Brown et al, 2012;Schramm et al, 2012) and non-coding RNAs (Xiong, Bing & Guo, 2019;Yang, Xu & Zeng, 2018) were reported to be involved in the prognosis of CM. Further laboratory studies aimed to investigate the potential molecular mechanisms of synchronous MPM occurrence and its prognostic roles are also in need.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the potential pathology of synchronous MPM needs to be illustrated in the future. Furthermore, many molecular events such as mutation (Demunter et al, 2001;Griewank et al, 2014), copy number variation (Rákosy et al, 2010;Gerami et al, 2011), epigenetic variation (Roh et al, 2016;Wouters et al, 2017), expression of genes (Brown et al, 2012;Schramm et al, 2012) and non-coding RNAs (Xiong et al, 2019;Yang et al, 2018) were reported to be involved in the prognosis of CM. Further laboratory studies aimed to investigate the potential molecular mechanisms of synchronous MPM occurrence and its prognostic roles are also in need.…”
Section: Discussionmentioning
confidence: 99%